2016
DOI: 10.1007/s00394-016-1245-6
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of l-alanine or l-arginine supplementation against adiposity and glucose intolerance in monosodium glutamate-induced obesity

Abstract: Ala supplementation led to more pronounced metabolic improvements compared to Arg, possibly due to suppression of lipogenesis through activation of the AMPK/ACC pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 43 publications
1
28
1
Order By: Relevance
“…Insulin resistance and reduced glucose tolerance in rodents due to MSG consumption raise concerns about the development of obesity in MSG consuming humans. The same study revealed that MSG intake causes a disrupted energy balance by increasing the palatability of food and disturbing the leptin-mediated hypothalamus signalling cascade, potentially leading to obesity (Araujo et al, 2017[ 2 ]; He et al, 2011[ 5 ]). In a study into the inflammatory profile of MSG induced obesity, it has been shown that MSG triggers micro-RNA (mRNA) expression of interleukin-6 (IL-6), tumour necrosis factor-alpha (TNF-α), resistin and leptin in visceral adipose tissue.…”
Section: mentioning
confidence: 99%
“…Insulin resistance and reduced glucose tolerance in rodents due to MSG consumption raise concerns about the development of obesity in MSG consuming humans. The same study revealed that MSG intake causes a disrupted energy balance by increasing the palatability of food and disturbing the leptin-mediated hypothalamus signalling cascade, potentially leading to obesity (Araujo et al, 2017[ 2 ]; He et al, 2011[ 5 ]). In a study into the inflammatory profile of MSG induced obesity, it has been shown that MSG triggers micro-RNA (mRNA) expression of interleukin-6 (IL-6), tumour necrosis factor-alpha (TNF-α), resistin and leptin in visceral adipose tissue.…”
Section: mentioning
confidence: 99%
“…Animal studies demonstrated neonatal MSG consumption caused obesity along with Insulin resistance and reduced glucose tolerance in later life of rodents. 4 In a placebo control study using MSG dose ranging from 57 -150 mg/kg was resulted in muscle pain and change in mechanical sensitivity in human. 5 Scientists have reported high dose of MSG 75 gms per kg in human elevates systolic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence shows that physiological levels of arginine and NO decrease fat synthesis and promote the oxidation of fat in a tissue-specific manner [ 79 ]. L-arginine has been reported to prevent body fat accumulation in DIO by regulating pancreatic β-cell physiology [ 80 ]. Supplementation of arginine reduces adiposity and improves glucose tolerance in obese rodents and humans [ 81 ].…”
Section: Discussionmentioning
confidence: 99%